Emotional Intelligence in Classrooms - Rawian, Rafizah Mohd (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2018)
The 21st century learning requires educators and learners to move beyond traditional academic learning. The fundamental aspects of the Ã¢â‚¬Å“Four CsÃ¢â‚¬Â (communication, critical thinking and problem solving, creativity and collaboration) are a prerequisite for the 21st century classrooms. LearnersÃ¢â‚¬â„¢ emotions in classrooms are now regarded as essential. The study of emotions in classrooms is central to understand learnersÃ¢â‚¬â„¢ motivation and learning patterns. Nelson and Low (2003) defined emotional intelligence as a confluence of developed skills and abilities to: (1) accurately know oneself in terms of personal strengths and weaknesses; (2) establish and maintain effective and healthy relationships; (3) get along and work productively with others; and (4) deal effectively and healthily with the demands and pressures of daily living. In other words, emotional intelligence is essential to effectively manage behaviours, to navigate social situations and to make decisions. This paper discusses the significant role of emotional intelligence in classrooms as well as the effective ways to enhance learnersÃ¢â‚¬â„¢ emotional intelligence.